Interface agent modified by ternary polymers for ceramic tile of old walls based on grey relational analysis - Guanji Lyu; Mingxin Zheng; Tao Ji; Yalin Ma (PLoS ONE, 2025)
The Interface Agent for Old Wall Tiles (IAWT) is an environmentally friendly material. However, its application in engineering is limited by its tendency to lose adhesion under harsh conditions. Factors such as freeze-thaw cycles, wind vibrations, rainfall, and thermal stress negatively affect the bond strength of IAWT. This study investigated the effects of PTB emulsion on various properties of IAWT, including bond strength, freeze-thaw resistance, wind vibration resistance, compressive-flexural ratio, water absorption, and microstructure. Orthogonal experiments were conducted to examine the impact of three key factors on the macroscopic properties of IAWT. The results indicated that increasing the ratio of PTB emulsion to water (P/W) improved bond strength under normal environmental conditions and enhanced freeze-thaw and wind vibration resistance. Furthermore, a higher P/W ratio reduced both the compressive-flexural ratio and water absorption. The addition of PTB emulsion slowed the hydration reaction, increased the number of micropores, and reduced the cumulative pore volume. Furthermore, it enhances the bond strength between the coating and the base layer, thereby increasing the durability of the renovation project for old walls. These enhancements yield positive economic and environmental benefits.